2012
DOI: 10.4018/ijeoe.2012010104
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian Bounds and a Heuristic for the Two-Stage Capacitated Facility Location Problem

Abstract: In the two-stage capacitated facility location problem, a single product is produced at some plants in order to satisfy customer demands. The product is transported from these plants to some depots and then to the customers. The capacities of the plants and depots are limited. The aim is to select cost minimizing locations from a set of potential plants and depots. This cost includes fixed cost associated with opening plants and depots, and variable cost associated with both transportation stages. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Relaxation-based heuristics were proposed by Litvinchev and Ozuna (2012) to solve the SP-TSCFLP considering instances with up to 10 plants and depots and 100 customers, while metaheuristcs were recently employed by Fernandes et al (2014) A wide set of large-sized instances was proposed by Fernandes et al (2014), who also proposed a GA to solve the SP-TSCFLP. Two heuristics proposed by Litvinchev and Ozuna (2012) (state of the art so far) were also applied to the new proposed set of instances, as well as a commercial solver. The authors demonstrated that GA was capable of outperforming both heuristics and solver.…”
Section: Sp-tscflp-single Productmentioning
confidence: 99%
See 1 more Smart Citation
“…Relaxation-based heuristics were proposed by Litvinchev and Ozuna (2012) to solve the SP-TSCFLP considering instances with up to 10 plants and depots and 100 customers, while metaheuristcs were recently employed by Fernandes et al (2014) A wide set of large-sized instances was proposed by Fernandes et al (2014), who also proposed a GA to solve the SP-TSCFLP. Two heuristics proposed by Litvinchev and Ozuna (2012) (state of the art so far) were also applied to the new proposed set of instances, as well as a commercial solver. The authors demonstrated that GA was capable of outperforming both heuristics and solver.…”
Section: Sp-tscflp-single Productmentioning
confidence: 99%
“…In addition, we note a lack of research in applying metaheuristics to solve the problem. Litvinchev and Ozuna (2012) proposed a mathematical model for SP-TSCFLP. The same model was used by Rabello et al (2016) and Biajoli et al (2019).…”
Section: Mp-tscflp-multiple Productsmentioning
confidence: 99%
“…Moreover, the latter work considers that the number of depots to locate is known beforehand. The TSCFLP version considered in this paper is the same of Litvinchev and Ozuna (2012) who proposed several Lagrangian relaxations for the problem. Feasible solutions are constructed from those of the Lagrangian subproblems by applying simple heuristic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Among some publications involving location and inventory problems we can mention the work of Tancrez [5], which incorporates the Economic Order Quantity Model (EOQ) into the facility location problem, assuming deterministic demand and fixing the lot size. References [4,6,7,8] present similar problems, but assume stochastic demands. Hernández et al [9] develop an algorithm to solve multi item inventory decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding to solution methods, the literature is not very extensive. The Lagrangian relaxation is the most appealed tool for solving problems with similar characteristics [8], but heuristics have also been used [7,10].…”
Section: Introductionmentioning
confidence: 99%